VITAMIN D STATUS AND SUPPLEMENTATION IN DENTAL IMPLANT OUTCOMES: A NARRATIVE REVIEW - Palus, Alicja; Dobrowolska, Julia; Krężołek, Marta; Kaczmarczyk, Paula; Zynek, Oliwia; Pawlak, Kornel; Stępiński, Marcin; Balicki, Mateusz; Kamyszek, Filip; Arkuszyński, Tomasz (International Journal of Innovative Technologies in Social Science, 2026)
Introduction: Dental implant therapy is widely used in modern restorative dentistry. However, its success depends on effective osseointegration, which may be influenced by systemic factors such as vitamin D status. Vitamin D plays a key role in bone metabolism, calcium-phosphate homeostasis, and immune regulation, all of which are essential for proper bone healing. Methods: This narrative review synthesizes current evidence on the role of vitamin D in dental implant osseointegration and outcomes. A literature search was conducted using PubMed, Google Scholar, and ResearchGate databases, focusing on studies published between 2020 and April 2026. Clinical trials, observational studies, and systematic reviews were included, and data were analyzed narratively. Results: The analyzed studies demonstrated heterogeneous findings. Most evidence suggests that adequate serum vitamin D levels and supplementation in deficient individuals may improve early implant stability and peri-implant bone healing. Vitamin D deficiency has been associated with impaired osseointegration and an increased risk of early implant failure. However, several studies did not confirm a statistically significant relationship. Additionally, emerging evidence indicates that excessively high vitamin D levels may also negatively affect implant outcomes. Conclusions: Most available evidence suggests that adequate vitamin D levels may support osseointegration, bone remodeling, and implant stability, while deficiency is associated with impaired healing and an increased risk of complications. However, the overall findings remain heterogeneous, and both insufficient and excessive levels may negatively affect outcomes. Assessment of vitamin D status prior to implant placement may therefore be beneficial, particularly in patients at risk of deficiency. Further well-designed clinical studies are required to establish optimal serum 25(OH)D levels and evidence-based supplementation protocols.